Diffusion weighted imaging changes in extra-abdominal desmoid tumor after cryotherapy. (31st December 2023) - Cadour, Farah; Tradi, Farouk; Bartoli, Axel; Duffaud, Florence; Gaubert, Jean-Yves
Abstract: Desmoid tumors (DT) are rare benign tumors with a local invasion potential and recurrence. It is characterized on histology by an abnormal fibroblastic proliferation in a collagenous stroma, in variable proportions leading to heterogeneity of the lesion signal on magnetic resonance imaging (MRI). Current guidelines propose watchful waiting but in case of progression or symptoms, cryotherapy may be a therapeutic option in its extra-abdominal form. Tumor recurrence is mostly detected based on post-contrast magnetic resonance imaging (MRI). Although DWI sequence is the key-sequence for tumor detection in oncologic imaging, there are very few data in literature on diffusion weighted imaging (DWI) in DT generally and even fewer on DT after cryotherapy. DWI changes after cryotherapy may be confusing and suspicious of residual tumor or tumor recurrence when displaying low ADC values; thus knowledge of possible DWI patterns after cryotherapy of DT seem paramount. We found that the early changes of DT after cryotherapy are hyperintensity on DWI sequence with low ADC values (<1.00 × 10 −3 mm 2 /s), without corresponding enhancement and a later decrease in signal of the treated lesion on DWI. The freezing-thawing cycles of cryotherapy turn DT into gelatinous necrosis with a slow resorption rate, as reported in the only few studies referring of changes of DWI signals after cryotherapy, which are on renal and prostate models. Hyperintensity on DWI with low ADC values may be seen in early MRI follow-up after cryotherapy of extra-abdominal DT, corresponding with tumor necrosis changes and should not be mistaken with recurrence. KEY MESSAGES: Magnetic resonance imaging is the modality of choice for desmoid tumor (DT) follow-up, mainly based on contrast uptake which make data on diffusion weighted imaging (DWI) very rare. Cryotherapy is an accepted therapeutic option for DT that will lead to tumor necrosis. Hyperintensity on DWI with low apparent diffusion coefficient values is a possible expected early pattern on DWI after cryotherapy of DT.